El Coaching como herramienta para mejorar el Desarrollo Empresarial de las pymes del sector comercio del distrito de Tarapoto – 2014 - Mogollón Llontop, Carmen Fabiola (2015)
This research, involves the purpose of evaluating and coaching becomes a tool to improve the business development of SMEs in the retail sector of the district of Tarapoto, where he developed and implemented a survey of owners, managers or managers, to meet the objectives; To collect information, the universe of SMEs (127) working in this financial institution, a sample of ten (95) workers was obtained. Methodologically descriptive research is applied. We study evaluated whether managers of SMEs have no knowledge of coaching as a tool to improve business performance. A notorious ignorance about coaching as a tool was obtained as a result. It was also noted that companies that apply this tool have increased business development and improving performance across the organization to fulfill its goals. Finally, it was concluded that few entrepreneurs who know the coaching and if they know the empirical manea apply. It also shows that coaching is establishing itself as an important tool in the world of business management which manages better human talent leading the company to achieve better results. Coaching as a management tool of human talent is particularly important that every team, workgroup and companies generally should be applied to make the most of all the members and make achievements contiguously.